Fernand Oury, figure inspirante ou identificatoire ? - Arnaud Dubois; Frédéric Canac; Patrick Geffard (Éducation et Socialisation)
The authors reflect on the notion of the ‘inspirational figure’ and its relevance to Fernand Oury, cofounder of institutional pedagogy. Drawing on a psychoanalytically oriented clinical approach, they suggest that this pedagogue should be considered more as an ‘identifying figure’. Rather than focusing on an individual figure, they suggest that the monographs of institutional pedagogy are ‘inspiring’. An analysis of a text published by F. Oury shows that, from the outset, institutional pedagogy has been a vehicle for a form of ‘democratic socialisation’ likely to challenge the ‘school form’.